IMPACT OF SOCIAL MEDIA ON LIBRARY SERVICES AND USER ENGAGEMENT - Henez, Zahida (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of this study is to investigate the dynamic and diverse function that social media plays in modern libraries, with a particular focus on the impact that it has on communication, outreach, and community participation. As libraries continue to become more adept at navigating the digital world, social media platforms have evolved into indispensable instruments for the dissemination of information, the promotion of resources, and the development of meaningful connections with library users. From the use of Facebook, Instagram, Twitter, and YouTube, this paper offers a conversation on the influence that interaction with social media has on library visits and user satisfaction. A study of 500 library customers produced the information, which provided statistical data on demographics, social media involvement score, and degree of satisfaction. Outcomes The study made clear that there were indeed good links between library visits and social media activity, especially on Facebook. Though there was variation in user satisfaction across platforms, YouTube appeared to be the most effective in generating involvement. The data indicate that interactive material and rich multimedia on social media could help libraries reach more people. The target audience for this would be much younger and mostly female. This study might eventually enhance the user experience and involvement as well as guide libraries in simplifying their social media initiatives.